Epidemiology and treatment patterns of essential tremor: a retrospective cohort analysis in Germany - Becktepe, Jos S.; McDonald, Keltie; Müller, Sabrina; Wilke, Thomas; Zhuleku, Evi; Appiah, Karen; Dzimitrowicz, Natasha; Marshall, Jade; Sabater, Javier; Barbato, Luigi M.; Saifee, Tabish A. (Frontiers in Neurology, 2025)
BackgroundReal-world evidence on the epidemiology, clinical characteristics, and treatment patterns of patients with essential tremor (ET) is limited. We used data from two large representative German claims databases to address this evidence gap.MethodsData were obtained from two German statutory health insurance databases, AOK PLUS and GWQ ServicePlus, from January 1, 2010 to March 31, 2022. Point prevalence and cumulative incidence of ET, standardized by age and sex to the German national population, were assessed. Baseline demographics, clinical characteristics, and treatment patterns were described within a cohort of patients newly diagnosed with ET in each database. Time to treatment initiation from diagnosis, and discontinuation and switch from the first-line therapeutic approach were evaluated using Kaplan Meier methods.ResultsAge and sex-standardized prevalence of ET increased between 2010 and 2021, reaching 196 (AOK) and 250 (GWQ) per 100,000 persons in 2021. Among patients newly diagnosed with ET, the most frequent comorbidities at baseline were pain disorders (65–70%), hypertension (44–65%), and hyperlipidaemia (30–35%). Approximately 60% of patients received pharmacological therapy during follow-up (mean 56–62 months), particularly propranolol (44–50%), bisoprolol (24–27%) and metoprolol (23–27%). The median time from diagnosis to treatment initiation was 2.1–6.3 months. Most patients discontinued (72–75%) their first therapy within 12 months, with 41–46% switching to another therapy.ConclusionET is a common movement disorder, the management of which is multi-faceted. Further evidence is needed to better understand and prioritize unmet needs and improve outcomes for patients with ET.